2014 Third International Workshop on Building Analysis Datasets and Gathering Experience Returns for Security (BADGERS) 2014
DOI: 10.1109/badgers.2014.14
|View full text |Cite
|
Sign up to set email alerts
|

EyeBit: Eye-Tracking Approach for Enforcing Phishing Prevention Habits

Abstract: This paper proposes a cognitive method with the goal to get end users into the habit of checking the address bar of the web browser. Earlier surveys of end user behavior emphasized that users become victims to phishing due to the lack of knowledge about the structure of URLs, domain names, and security information. Therefore, there exist many approaches to improve the knowledge of end users. However, the knowledge gained will not be applied unless end users are aware of the importance and develop a habit to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Mobile users are even more oblivious of their presence when dealing with the reduced screens of their smartphones [25]. Indeed, there is no objection to the increased security brought by using SSL/TLS in HTTP communications, and research works specifically aiming to educate users into recognizing security icons [26] should be encouraged. But even security-savvy users may fall victims to phishing traps if they do not use their discernment when dealing with seemingly secure websites.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile users are even more oblivious of their presence when dealing with the reduced screens of their smartphones [25]. Indeed, there is no objection to the increased security brought by using SSL/TLS in HTTP communications, and research works specifically aiming to educate users into recognizing security icons [26] should be encouraged. But even security-savvy users may fall victims to phishing traps if they do not use their discernment when dealing with seemingly secure websites.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to better understand the mechanisms behind a successful phishing attack. By using eye tracking it is possible to explore what factors predict whether someone will be tricked by a phishing website, by considering the interaction between the structure of the website and what the person looks at, or indeed fails to look at (Miyamoto et al, 2014). This has been used for example to understand how and if users pay attention to web browser security indicators, such as the Firefox Mozilla SSL certificate (Sobey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Further uses of eye tracking in cybersecurity have become evident as the research field and technology have continued to develop. For instance it has been demonstrated that the technology can be used to change risky behaviors, such as for example by preventing a user from continuing with use of input forms in a website unless an eye tracker has determined that the individual has looked at the address bar (Miyamoto et al, 2014). Similarly, eye trackers can be used to detect anomalous user behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers are now experimenting with active applications of eye-tracking. Miyamoto et al [17] have developed EyeBit-an eyetracking based system to inculcate the habit of looking at the URL address bar before entering sensitive information in the website's input fields, in order to prevent phishing. The system first deactivates the input fields in a website, and using the eye-tracking data determines if the user has looked at the website's URL.…”
Section: Eye-tracking For User Attention and Comprehensionmentioning
confidence: 99%
“…The decision buttons are initially deactivated, and once the user reads and scrolls down on the policy, they are activated. Second is an eye-tracking based mechanism to put the user into the habit of looking at the URL address bar to determine the website's legitimacy before entering sensitive information [17]. The input fields are initially deactivated, and once the user looks at the URL address (determined using the eyegaze fixations on the URL address bar screen coordinates), they are activated.…”
Section: Introductionmentioning
confidence: 99%